2008
DOI: 10.1080/09546630701243418
|View full text |Cite
|
Sign up to set email alerts
|

Review of antifungal therapy and the severity index for assessing onychomycosis: Part I

Abstract: This review outlines recent data on treatment modalities and outcomes with antifungal therapy in onychomycosis. Included are topical, mechanical, chemical and systemic treatments or a combination thereof. Topical treatments, or transungual drug delivery systems (TUDDS), including ciclopirox and amorolfine were shown to be effective if used alone for mild-moderate nail involvement. Specifically, superficial white onychomycosis (SWO) restricted to the dorsum of the nail plate and moderate distal lateral subungua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 51 publications
1
54
0
3
Order By: Relevance
“…0001) [20]. While trauma has been also cited as a sign of poor prognosis [12,15], there have been no large-scale studies evaluating the association of trauma with response to treatment.…”
Section: Patient Characteristics and Morbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…0001) [20]. While trauma has been also cited as a sign of poor prognosis [12,15], there have been no large-scale studies evaluating the association of trauma with response to treatment.…”
Section: Patient Characteristics and Morbiditiesmentioning
confidence: 99%
“…These are shown in Table 1 [11][12][13][14][15][16][17]. Patient characteristics include older age, prior trauma to the affected nail, and previous history of onychomycosis; patient morbidities include immunosuppression, poor peripheral circulation, and uncontrolled diabetes mellitus.…”
Section: Poor Prognostic Factors For Onychomycosismentioning
confidence: 99%
“…53,54 Exposure up to 23 weeks' gestation can cause severe neonatal dysmorphic features including craniosynostosis, cleft palate, humeral-radial fusion, bowed tibia and femur, hypoplasia of the nasal bones, and short thumbs and toes in women receiving fluconazole at doses of $400 mg daily during the first trimester of pregnancy. A number of studies have reported a lack of congenital defects among infants delivered by women exposed to short courses of lower doses of fluconazole, including when given during the first trimester.…”
Section: Antifungal Therapymentioning
confidence: 99%
“…Itraconazole is widely used in the treatment of superficial and invasive fungal infections [11,12]. It is a potent and specific inhibitor of CYP3A and it has been the cause of clinically significant drug-drug interactions with many substrates of CYP3A [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%